2016
DOI: 10.1016/j.pneumo.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

La silicotuberculose

Abstract: Silicosis increases the risk of tuberculosis, hence the importance of TB screening in all patients with silicosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Pulmonary tuberculosis represents an important global public health problem and is the main silicosis comorbidity . Silica exposure is an important risk factor to Tb development, but none of the extrinsic factors related to silicosis development were associated with Tb in the present work (years of exposure to silica P = .902, hours of exposure to silica per week P = .936, and years since last exposure to silica P = .289). Smoking also showed no difference in the distribution between the groups ( P = .482).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Pulmonary tuberculosis represents an important global public health problem and is the main silicosis comorbidity . Silica exposure is an important risk factor to Tb development, but none of the extrinsic factors related to silicosis development were associated with Tb in the present work (years of exposure to silica P = .902, hours of exposure to silica per week P = .936, and years since last exposure to silica P = .289). Smoking also showed no difference in the distribution between the groups ( P = .482).…”
Section: Discussionmentioning
confidence: 62%
“…The complications associated with crystalline silica inhalation go beyond silicosis. Individuals exposed to silica show 3.7 fold higher susceptibility to tuberculosis (Tb) than nonexposed subjects, while silicosis patients have approximately a 40 fold greater risk for Tb . However, the way that crystalline silica influences the pathogenicity of Mycobacterium tuberculosis (MTb) is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…La lésion radiologique n'est pas spécifique, cependant, des lésions séquellaires y sont observées (atélectasies à droite). En effet, la tuberculose est citée dans la majorité des études comme l'une des principales complications de la silicose (Ellidrissi et al, 2016 ;Elkard et al, 2016 ;Heddane et al, 2019). D'autres complications comme le pneumothorax, l'insuffisance respiratoire chronique et le coeur pulmonaire chronique sont également très fréquemment rencontrés (Heddane et al, 2019), en sachant qu'elles sont toutes observées chez nos patients.…”
Section: Discussionunclassified
“…Autopsy studies revealed that QIS is associated with pulmonary carcinoma, with positive correlation between Q exposure frequency and pulmonary cancer incidence. Lung pathology incidence increases if Q air concentration reaches 2mg/m3 [15,16,17,18,19,20,21] .…”
Section: Introductionmentioning
confidence: 99%